Implementasi Pembentukan Komponen Cadangan Pertahanan Negara Kementerian Pertahanan Republik Indonesia di Kodam III/Siliwangi Provinsi Jawa Barat - Tjetjep Darmawan; Sunarno Sunarno (CV. ULIL ALBAB CORP, 2024)
The purpose of the study is to analyze the Implementation of the Formation of Reserve Components in supporting state defense in Kodam III/Siliwangi, West Java Province. This study uses a descriptive qualitative research method. Data collection techniques with observation, interviews, documentation and literature studies. The data obtained from the informants that have been determined using the purposive sampling technique are then analyzed by analysis techniques, namely data reduction, data presentation, source tringulation and conclusion drawn. The results of the study show that the implementation of the formation of the reserve component has been optimally implemented because the participants of the reserve component already have the capacity and expertise to support the strengthening of state defense. From these data, it can be concluded that Kodam III/Siliwangi carries out the formation of a reserve component (komcad) in accordance with Law Number 23 of 2019 concerning National Resource Management for State Defense and can massively continue to increase the socialization of the formation of Komcad in the West Java region. The suggestion that can be given from this conclusion is the need for sustainable coaching for reserve component graduates (komcad) in supporting the strengthening of the country's defense.